Response of Vegetables to NPK Briquette Deep Placement - Choudhury, Apurba Kanti; Sarker, Md. Jalal Uddin; Rashid, Md. Harunur; Sarker, Md. Mamunur Rashid; Shahduzzaman, Md.; Islam, Md. Sirajul; Bashar, H. M. Khairul (Agriculture and Natural Resources, 2015)
The performance was evaluated during April to November, 2012 of the deep placement of NPK fertilizer briquettes compared with broadcast incorporation of N, P, and K, with each treatment supplying S, Zn and B fertilizers as a blanket dose, for vegetables like cucumber, taro and bitter gourd. The experiments were conducted under on-station and on-farm conditions in three locations in Bangladesh: at Jessore for cucumber, at Patuakhali for bitter gourd and for taro at Mymensingh (only on-farm) and at Jessore (only on-station). Six treatments were designed to evaluate the crop responses to: the broadcast incorporation of N, P, and K applied as prilled urea (PU), triple super phosphate (TSP), and muriate of potash (MOP); deep placement of urea briquettes and NPK briquettes; native fertility; and general farmer practice. The size of the NPK briquettes and the urea briquettes was 3.4 g and 1.8 g, respectively. The results showed that deep placement of the NPK briquettes gave higher vegetable yields (28.8% for cucumber, 25.6% for taro and 10.8% for bitter gourd) and higher gross margins over broadcast incorporation of N, P, and K. The amount of NPK nutrient uptake and recovery by all three vegetable crops was also higher in the NPK briquette treatment compared to the broadcast treatment with PU, TSP and MOP.